Impact of Grid Refinement on a Non-Conventional Mesh Structure: A Case Study with INSIM-FT - López, Dimary Moreno; Teixeira, João; Pesco, Sinesio; B. Junior, Abelardo B.; Rodrigues, José R. P.; Alves, Regina; Cavalcante, Rodrigo Gusmão; Grave, Malú (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2025: Anais Estendidos da XXXVIII Conference on Graphics, Patterns and ImagesDO - 10.5753/sibgrapi.est.2025.38321, 2025)
To support decision-making, the oil and gas industry relies on flow simulators to evaluate multiple production scenarios. This demands simulation tools that are both accurate and computationally efficient. INSIM-FT (Interwell Numeric Simulation Model with Front-Tracking) is a hybrid flow simulator that combines physical modeling with data-driven components, using a non-conventional mesh built through Mitchell’s Best Candidate algorithm and Delaunay Triangulation. Although finer meshes are expected to improve spatial representation, they also increase computational costs and may interfere with the performance of data-driven elements. This trade-off highlights the need to assess the influence of the number of imaginary nodes used in INSIM-FT. This work investigates how mesh configuration impacts the accuracy and performance of the simulator through a case study of a heterogeneous reservoir. Considering randomly generated models whose parameters are adjusted by the datadriven component, the results show that mesh refinement affects the spread of the adjusted prior models around the mean. Nevertheless, the mean of the simulations remains reasonably close to the observed data in all cases.